أسس وتطبيقات منهج تربية الرسول صلى الله عليه وسلم في تربية البنات ما قبل الزواج وما بعدها - Muhammad Fakhar Moeen; Hafiz Haris Saleem (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2020)
The human society consists of two main pillars; male and female. Islam balanced mankind by addressing the issue of a female in a society and showed her duties and role in a society. The most happy Muslim family is the family which takes care of its children and raise them according to good morals. Raising a baby regardless of her sex is very important but raising a female baby needs some highest level of attention. Marriage is one of the very important event in Muslim society which is Sunnah of Prophet Muhammad PBUH. Islam gave much importance to marriage as well because its foundation of a family. Raising a female member of a family is a responsibility given by Islam to every parent. In view of this topic I have decided to write about Prophet PBUH methodology about raising a female child. Descriptive and Applied method is used in this Article. Keywords: Human Society, Muslim Family, Responsibility, Female baby, Parent.